Field monitoring of vibration characteristics during advanced ductule installation in sandy cobble stratum - Kang, Jiawei; Deng, Guohua; Zhang, Kai; Shao, Shengjun (Frontiers in Earth Science, 2023)
The sandy cobble stratum presents a high risk for underground tunnel construction due to its low cohesive properties and susceptibility to loosening and falling. The use of Advanced ductule for grouting reinforcement inevitably results in vibrations, and understanding how these vibrations propagate is crucial in selecting tunnel engineering support schemes and responding to accident risks. Based on a bored tunnel under construction in Xi'an, field vibration propagation characteristics testing were carried out for advanced ductile installation.The time-history response and frequency distribution characteristics of the vibration velocity within the tunnel face under sandy cobble stratum conditions were studied, and the law of vibration propagation attenuation within the tunnel face range was obtained.The results showed that: 1) During the conduit drilling process, the tunnel face mainly experienced vertical vibrations, with the horizontal velocity amplitude accounting for only 15% to 20% of the vertical velocity amplitude. At a distance of 1.0m from the conduit, the vertical velocity amplitude reaches 10.602mm/s, and the vibration energy concentrates mainly in the frequency range of 150-250Hz. At a distance of 1.5m from the conduit, the bidirectional vibration velocity significantly attenuates; 2) The vibration characteristics within the tunnel face can be classified into three primary areas: "Loose and Falling" area, "Significant Vibration" area, and "Vibration Attenuation" area. Loose、falling and significant vibrations occurred mainly within a range of about 1.25m around the conduit. 3) As the diameter of the conduit decreases, the amplitude of vertical vibration velocity decreases by about 20%.